PSA Doubling Time Versus PSA Velocity to Predict High-Risk Prostate Cancer: Data from the Baltimore Longitudinal Study of Aging - Loeb, Stacy (2008)
BACKGROUND: Our group has previously shown that prostate-specific antigen (PSA) velocity (PSAV) is associated with the presence of life-threatening prostate cancer. Less is known about the relative utility of pretreatment PSA doubling time (PSA DT) to predict tumor aggressiveness. OBJECTIVE: To compare the utility of PSAV and PSA DT for the prediction of life-threatening prostate cancer. DESIGN, SETTING, AND PARTICIPANTS: From the Baltimore Longitudinal Study of Aging, we identified 681 men with serial PSA measurements. MEASUREMENTS: Receiver operating characteristic analysis was used to evaluate the relationship between PSAV, PSA DT, and the presence of high-risk disease. RESULTS AND LIMITATIONS: Within the period of 5 yr prior to diagnosis, PSAV was significantly higher among men with high-risk or fatal prostate cancer than men without it. By contrast, PSA DT was not significantly associated with high-risk or fatal disease. On multivariate analysis, including age, date of diagnosis, and PSA, the addition of PSAV significantly improved the concordance index from 0.85 to 0.88 (p < 0.001), whereas PSA DT did not. CONCLUSIONS: These data suggest that PSAV is more useful than PSA DT in the pretreatment setting to help identify those men with life-threatening disease.